Analisis Penerapan Batas Maximum Kepemilikan Tanah Terhadap Pulau-Pulau Kecil - Petrus Julianro Rato; Maria Yovita Naif; Benediktus Peter Lay (Madani: Jurnal Ilmiah Multidisiplin, 2023)
As a gift from God, land is the pioneer of civilization for every society because it has philosophical and historical aspects in each region as well as a strategic natural resource for the nation, state and people. Land is a means to achieve social welfare for the Indonesian nation so it needs state intervention to regulate it. This is by the constitutional mandate and as the political basis for national agrarian law as stated in Article 33 paragraph (3) of the 1945 Constitution which states that the natural resources contained therein are controlled by the state and used for the greatest prosperity of the people. . the author uses the normative juridical research method. This study uses a state-approach problem approach (State-Approach) related to what the researcher wants to examine. The data and information for this research are primary and secondary data, which have been made available through laws, journals, books, and other factual supporting sources. Soil is the plains that are above the surface of the earth that can be used to carry out human life. Soil is very valuable where the amount cannot increase or decrease therefore it is very valuable for human life to survive. Land Rights to Small Islands Permen Agraria 17/2016 stipulates that small islands can be given land rights. Application of Maximum Limits on Land Ownership for Small Islands Land which is a natural resource is a gift from God Almighty for it to be utilized for the prosperity of mankind. Regulations regarding islands (mention the rules above regarding islands) do not contradict Article 7 and Article 17 of the UUPA number 5 of 1960 which regulates difficulties with the land because the regulations governing islands already provide provisions that limit parties from individually managing the entire island.